Bacterial death from treatment with fluoroquinolones and other lethal stressors. Issue 5 (4th May 2021) - Drlica, Karl; Zhao, Xilin
ABSTRACT: Introduction: Lethal stressors, including antimicrobials, kill bacteria in part through a metabolic response proposed to involve reactive oxygen species (ROS). The quinolone anti-bacterials have served as key experimental tools in developing this idea. Areas covered: Bacteriostatic and bactericidal action of quinolones are distinguished, with emphasis on the contribution of chromosome fragmentation and ROS accumulation to bacterial death. Action of non-quinolone antibacterials and non-antimicrobial stressors is described to provide a general framework for understanding stress-mediated, bacterial death. Expert opinion: Quinolones trap topoisomerases on DNA in reversible complexes that block DNA replication and bacterial growth. At elevated drug concentrations, DNA ends are released from topoisomerase-mediated constraint, leading to the idea that death arises from chromosome fragmentation. However, DNA ends also stimulate repair, which is energetically expensive. An incompletely understood metabolic shift occurs, and ROS accumulate. Even after quinolone removal, ROS continue to amplify, generating secondary and tertiary damage that overwhelms repair and causes death. Repair may also contribute to death directly via DNA breaks arising from incomplete base-excision repair of ROS-oxidized nucleotides. Remarkably, perturbations that interfere with ROS accumulation confer tolerance to many diverse lethal agents.